Mismatch repair systems might facilitate the chromosomal recombination induced by N-nitrosodimethylamine, but not by N-nitrosodiethylamine, in Drosophila. (28th February 2020) - Negishi, Tomoe; Yamada, Kenji; Miyamoto, Keiko; Mori, Emiko; Taira, Kentaro; Fujii, Asei; Goto, Yuki; Arimoto-Kobayashi, Sakae; Okamoto, Keinosuke
Abstract: Mismatch repair (MMR) systems play important roles in maintaining the high fidelity of genomic DNA. It is well documented that a lack of MMR increases the mutation rate, including base exchanges and small insertion/deletion loops; however, it is unknown whether MMR deficiency affects the frequency of chromosomal recombination in somatic cells. To investigate the effects of MMR on chromosomal recombination, we used the Drosophila wing-spot test, which efficiently detects chromosomal recombination. We prepared MMR (MutS)-deficient flies ( spel1 (−/−)) using a fly line generated in this study. The spontaneous mutation rate as measured by the wing-spot test was slightly higher in MutS-deficient flies than in wild-type ( spel1 (+/−)) flies. Previously, we showed that N -nitrosodimethylamine (NDMA)-induced chromosomal recombination more frequently than N -nitrosodiethylamine (NDEA) in Drosophila. When the wing-spot test was performed using MMR-deficient flies, unexpectedly, the rate of NDMA-induced mutation was significantly lower in spel1 (−/−) flies than in spel1 (+/−) flies. In contrast, the rate of mutation induced by NDEA was higher in spel1 (−/−) flies than in spel1 (+/−) flies. These results suggest that in Drosophila, the MutS homologue protein recognises methylated DNA lesions more efficiently than ethylated ones, and that MMR might facilitate mutational chromosomal recombination due to DNA double-strand breaks via the futile cycle induced by MutS recognition of methylated lesions.